A PRELIMINARY INVESTIGATION ON EFFECTS OF TWO DIFFERENT CORTICAL- SCREW CONFIGURATIONS ON LOCKING PLATES FOR THE REPAIR OF SIMPLE DIAPHYSEAL LONG BONE FRACTURES IN DOGS - N. Kallianpur; K. Singh; A. Gopinathan; S. B. Sarangom; P. Sharma; C. Sowbharenya; C. John (Journal of Animal and Plant Sciences, 2019)
The study was conducted on 12 client-owned dogs to evaluate the effects of two different cortical-screw configurations on locking plate fixation in simple transverse diaphyseal long bone fractures. Dogs were randomly divided into 2 groups (n = 6). In group A, locking screws were placed in bicortical configuration and in Group B, bicortical screws were replaced by unicortical screws except at the distal most holes. There was no significant difference (P>0.05) between groups with respect to age; body weight; time lapse; preoperative soft tissue status; early postoperative weight bearing; and postoperative limb function, stance and gait scores during progression, pain on palpation and manipulation, lameness scores and fracture angulations at different intervals. The surgical procedures were successful in all dogs. The duration of surgery was significantly short (P≤0.05) in group B. Fractures in both groups healed by primary gap healing with minimum callus formation and the radiographic healing time in group A was non-significantly less (P>0.05). Major postoperative complications were plate breakage, dislodgement of plate with far bicortical screw head breakage, pull-out of adjacent unicortical screw, and enbloc screw pull-out. Retrospective evaluation of the failures ruled out the possible involvement of cortical-screw configuration. An overall functional recovery was excellent in both the groups. In terms of screw-related complications, the bicortical screw configuration was superior to the mixed screw-cortex configuration despite the fact that the failures were not associated with screw-cortex configuration. The discernible advantages of mixed screw-cortex configuration were the ease of application and short duration of surgery. The findings substantiate that fixation of locking plates using unicortical-bicortical screw configuration provide adequate stability and enable fracture healing similar to bicortical screw configuration in simple diaphyseal long bone fractures in dogs. Further studies are necessary prior to regularization of mixed screw-cortex configurations in clinical practice.
Keywords: Locking plate; long bone; bicortical screw; unicortical; locking screw; dog